Clinical particularities and response to the anti-inflammatory effect of antiviral treatment in patients with Chronic Hepatitis C and Rheumatoid Syndrome - Lilea, GC (Carol Davila University Press, 2012)
Hepatitis C virus (HCV) is an important cause for the development of serious hepatic disease such as chronic hepatitis and liver cirrhosis. Though the pathological mechanisms are poorly understood, it is well established that CHC plays an important role in several immune mediated conditions, including rheumatoid arthritis. We focused on the clinical particularities of patients with CHC and associated RS and we specifically investigated the anti-inflammatory role of IFN-alpha concerning the rheumatic symptoms.